UPAYA MENINGKATKAN KEAKTIFAN DAN MOTIVASI BELAJAR PESERTA DIDIK KELAS 4 SDN 1 BABADAN MELALUI METODE ROLE PLAYING BERBANTUAN GAME WORDWALL PADA PEMBELAJARAN PANCASILA - Siti Ummaroh; Al Amin (ADIBA : JOURNAL OF EDUCATION, 2026)
This study aims to determine whether the implementation of the Role Playing learning method assisted by the Wordwall game can increase the engagement and learning motivation of fourth-grade elementary school students in Pancasila education lessons. This study was conducted at SDN 1 Babadan. The research method used was descriptive qualitative, with 21 students as research subjects, consisting of 11 boys and 10 girls. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using qualitative descriptive methods. The results indicate an increase in student engagement and motivation following the implementation of the Role-Playing learning method supported by the Wordwall game in Pancasila education. This is evidenced by an increase in the number of students who dared to ask questions, answer questions, and actively participate in the games and role-playing activities. Based on these findings, it can be concluded that the Role-Playing learning method supported by the Wordwall game is proven effective in enhancing students’ engagement and learning motivation. The implications of this study highlight the importance of using innovative, technology-based learning methods to boost student engagement, create a more engaging learning environment, and motivate students to learn more actively and effectively.